Comparative evaluation of a fast in-situ droplet detector and water-sensitive paper for pesticide spray distribution assessment in crop protection operations - Shihui Yu; Jian Liu; Xianguo Huang; Lin Liu; Xuemei Liu; Zhenbo Xin; Jin Yuan; Geoffrey I.N. Waterhouse (Crop Protection, 2026)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Energy and carbon-efficient one-pot bioprocessing for upcycling non-sterile food waste into high-yield 2,3-butanediol production - Shazia Rehman; Aamir Khan; Chun-Yin Lau; Raffel Dharma Patria; Yvette Shihui Yang; Carol Sze Ki Lin; Duu-Jong Lee; Shao-Yuan Leu (Environmental Research, 2025)

Characteristics and Evaluation of Living Shorelines: A Case Study from Fujian, China - Xingfan Li; Shihui Lin; Libing Qian; Zhe Wang; Chao Cao; Qi Gao; Jiwen Cai (Journal of Marine Science and Engineering, 2025)
Under the context of global climate change, sea-level rise and frequent storm surge events pose significant challenges to coastal areas. Protecting coastlines from erosion, mitigating socio-economic losses, and maintaining ecosystem balance are critical for the sustainable development of coastal zones. The concept of “living shorelines” based on Nature-based Solutions (NbS) employs near-natural ecological restoration and protection measures. In low-energy coastal segments, natural materials are prioritized, while high-energy segments are supplemented with artificial structures. This approach not only enhances disaster resilience but also preserves coastal ecosystem stability and ecological functionality. This study constructs a coastal vitality evaluation system for Fujian Province, China, using the entropy weight method, integrating three dimensions: protective safety, ecological resilience, and economic vitality. Data from 2010 and 2020 were analyzed to assess the spatiotemporal evolution of coastal vitality. Results indicate that coastal vitality initially exhibited a spatial pattern of “low in the north, high in the center, and low in the south,” with vitality values ranging from 0.20 to 0.67 (higher values indicate stronger vitality). Over the past decade, ecological restoration projects have significantly improved coastal vitality, particularly in central and southern regions, where high-vitality segments increased markedly. Key factors influencing coastal vitality include water quality, cyclone intensity, biological shoreline length, and wetland area. NbS-aligned coastal management strategies and soft revetment practices have generated substantial ecological and economic benefits. To further enhance coastal vitality, region-specific approaches are recommended, emphasizing rational resource utilization, optimization of ecological and economic values, and the establishment of a sustainable evaluation framework. This study provides scientific insights for improving coastal protection capacity, ecological resilience, and economic potential.

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Breaking the vicious cycle of cellular senescence and ROS via a mitochondrial-targeted hydrogel for aged bone regeneration - Liangmin Fu; Shan Wang; Na Zhang; Yajing Lin; Shihui Zhang; Yingji Mao; Pinghui Zhou (Chemical Engineering Journal, 2025)

Behavioral and physiological responses of nocturnal marine shellfish to predation pressure - Qi Luo; Xiaolong Gao; Mo Zhang; Shihui Lin; Huiyang Huang; Miaoqin Huang; Caihuan Ke (Applied Animal Behaviour Science, 2024)

Effects of flow velocity on the muscle nutrient content and flesh quality of the Pacific abalone (Haliotis discus hannai) - Shihui Lin; Mo Zhang; Qi Luo; Miaoqin Huang; Caihuan Ke; Xiaolong Gao (Aquaculture, 2024)

Fluorescence detecting glycopeptide antibiotics via a dynamic molecular switch - Xiaomei Zou; Yanting Lin; Shihui Zhang; Tao Deng; Ximing Xu; Yingchun Zhou; Zhihui Liu; Weiguo Lu; Qingzhong Hu; Chaozhan Lin; Chenchen Zhu; Fang Liu (Analytica Chimica Acta, 2024)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

Substrate-related factors and kinetic studies of Carbohydrate-Rich food wastes on enzymatic saccharification - Shazia Rehman; Yvette Shihui Yang; Raffel Dharma Patria; Talha Zulfiqar; Noman Khalid Khanzada; Rabia Jalil Khan; Carol Sze Ki Lin; Duu-Jong Lee; Shao-Yuan Leu (Bioresource Technology, 2023)

Circadian feeding characteristics of different abalone species and construction of a gastrointestinal evacuation model - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Caihuan Ke (Aquaculture, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

Limestone hydrogenation combined with reverse water–gas shift reaction under fluidized and iso-thermal conditions using MFB-TGA-MS - Iwei Wang; Dan Li; Shihui Wang; Yang Wang; Gang Lin; Binhang Yan; Zhenshan Li (Chemical Engineering Journal, 2023)

Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Shihui Lin; Xiaolong Gao; Mo Zhang; Mingxin Lyu; Caihuan Ke (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, the Pacific abalone ( Haliotis discus hannai ) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or to forage, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help us to understand these rhythmic behaviors in the abalone species. In the present study, quantification of behavioral data for the abalone and its predator swimming crab Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggests that the distance and duration of movement, percentage of feeding individuals, and cumulative duration of feeding of the abalone individuals were significantly lower under the short-term predation risk than the long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK) in hemolymph, and expression levels of 5-HT1A receptor and 5-HT2 receptor in cerebral ganglion were significantly higher under the long-term predation risk than the short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen content in adductor muscle of the abalone was significantly higher under the short-term predation risk than the long-term predation risk, thereby implying their role in anaerobic metabolism and aerobic metabolism as primary energy sources under the short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under the short-term predation risk, but changes in the movement and feeding behaviors of the abalone still occurred at the night only. Correlation analysis shows that the expression levels of Bmal1 and Clock had significantly positive correlations with the circadian changes in the movement parameters of the abalone, thereby suggesting a dominant role in the rhythmic expression of endogenous circadian clock genes regulating the rhythmic behavior of the abalone. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals and a reference for developing rational stock enhancement plans, and would improve protection for marine benthic biodiversity.

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

Development of light-weight hollow constructional materials through microbial-induced calcium carbonate precipitation - Huang Wei; Kejun Wen; Shihui Liu; Lin Li; Farshad Amini (Arabian Journal of Geosciences, 2021)

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Mechanical properties of soft soils experiencing lateral unloading under initial excess pore water pressure - Wei Huang; Kejun Wen; Junjie Li; Xuemei Fu; Shihui Liu; Yang Li; Lin Li; Farshad Amini (Arabian Journal of Geosciences, 2020)

Transport and numerical simulation of Cu2+ in saturated porous medium in the presence of magnetic nanoparticles - Shihui Song; Yinghao Song; Mengdi Shi; Zheng Hu; Tianyu Li; Shanshan Lin (Environmental Science and Pollution Research, 2019)

Solution structure and backbone dynamics for S1 domain of ribosomal protein S1 from Mycobacterium tuberculosis - Biling Huang; Shihui Fan; Yan Liu; Yufen Zhao; Donghai Lin; Xinli Liao (European Biophysics Journal, 2019)

A Carbon Footprint of High‐Speed Railways in China: A Case Study of the Beijing‐Shanghai Line - Jianyi Lin; Huimei Li; Wei Huang; Wangtu(Ato) Xu; Shihui Cheng (Journal of Industrial Ecology, 2019)
Summary A carbon footprint (CF) assessment of Chinese high‐speed railways (HSRs) can help guide further development of the world's longest HSR network. In this research, a hybrid economic input‐output and life cycle assessment (EIO‐LCA) method was applied to estimate the CF of the Beijing‐Shanghai HSR line. Specific CFs were analyzed of different subsystems of the line, different stages of production, and three calculation scopes. Results showed that the annual CF of the Beijing‐Shanghai HSR is increasing, whereas the per‐passenger CF constantly declined between 2011 and 2014. Scope 1 emissions account for an average of 4% of the total annual CF, Scope 2 contribute 71%, and Scope 3 comprise 25%. Among the different stages, operation contributes the largest (71%), followed by construction (20%) and maintenance (9%). In the construction stage, the bridges have the largest CF, followed by trains, and then rails. A trade‐off exists between the increase in carbon emissions due to construction of bridges and the reduction in operation emissions affected by leveling changes in terrain. The Beijing‐Shanghai HSR line has a relatively higher per‐passenger CF than eight other HSR lines, which is largely due to China's coal‐based carbon‐intensive energy mix of electricity generation, high proportion of bridges, higher operating speed, and heavier train body. In the future, cleaner electricity supply options, more efficient raw material production, and improvement of trains are keys to reducing the CF of Chinese HSRs.

Development of an Improved Immersing Method to Enhance Microbial Induced Calcite Precipitation Treated Sandy Soil through Multiple Treatments in Low Cementation Media Concentration - Kejun Wen; Yang Li; Shihui Liu; Changming Bu; Lin Li (Geotechnical and Geological Engineering, 2019)

Co-Delivery of Ciprofloxacin and Colistin in Liposomal Formulations with Enhanced In Vitro Antimicrobial Activities against Multidrug Resistant Pseudomonas aeruginosa - Shaoning Wang; Shihui Yu; Yuwei Lin; Peizhi Zou; Guihong Chai; Heidi H. Yu; Hasini Wickremasinghe; Nivedita Shetty; Junhong Ling; Jian Li; Qi Zhou (Pharmaceutical Research, 2018)

Modulation of Brain Activities by Hierarchical Processing: A High-Density ERP Study - Shihui Han; Silu Fan; Lin Chen; Yan Zhuo (Brain Topography, 1999)